2013
DOI: 10.1159/000354892
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Gelatinase-Associated Lipocalin as a Biomarker of Acute Kidney Injury in Patients with Morbid Obesity Who Underwent Bariatric Surgery

Abstract: Introduction: Neutrophil gelatinase-associated lipocalin (NGAL) has been identified as a biomarker of acute kidney injury (AKI) that could contribute to early diagnosis and effective management of AKI. The purpose of this study was to evaluate NGAL as a predictive marker of AKI in patients with clinically severe obesity (BMI >50) who underwent biliopancreatic diversion surgery. Patients and Methods: We prospectively studied 23 patients with clinically severe obesity who underwent biliopancreatic bypass surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Importantly, with the resolution of acute kidney insult, these novel subclinical biomarkers of kidney injury decline to pre‐injury concentrations in the urine, demonstrating that these biomarkers are not permanently altered by a kidney insult but instead may be useful for tracking the resolution of the insult . Interestingly, one small adult study have reported development of clinical AKI within 2‐3 days after bariatric surgery which was associated with an increase in NGAL levels on the first postoperative day . We did not measure urinary biomarkers in the peri‐operative period however we did not observe clinically evident AKI in any of our subjects either.…”
Section: Discussionmentioning
confidence: 75%
“…Importantly, with the resolution of acute kidney insult, these novel subclinical biomarkers of kidney injury decline to pre‐injury concentrations in the urine, demonstrating that these biomarkers are not permanently altered by a kidney insult but instead may be useful for tracking the resolution of the insult . Interestingly, one small adult study have reported development of clinical AKI within 2‐3 days after bariatric surgery which was associated with an increase in NGAL levels on the first postoperative day . We did not measure urinary biomarkers in the peri‐operative period however we did not observe clinically evident AKI in any of our subjects either.…”
Section: Discussionmentioning
confidence: 75%
“…The studies evaluating the relationship between bariatric surgery and urinary NGAL levels are limited in the literature. Koukoulaki et al evaluated the effect of NGAL on acute kidney injury and observed that urinary NGAL levels increased before serum creatinine elevation in the first 24 hours after biliopancreatic diversion in patients with acute kidney injury (19). The comparison of NGAL levels with diabetic and nondiabetic patients after bariatric surgery is the strength of our study.…”
Section: Diabetic (N=10)mentioning
confidence: 81%
“…Другими биомаркерами повреждения почки являются Kim-1, RPA-1, цистатин С, остеопонтин и фибриноген. В экспериментальном исследовании показано, что такие биомаркеры, как альбумин, NAG, остеопонтин, фибриноген, значимо повышались при прогрессировании нефропатии у крыс с гипертензией и ожирением и коррелировали со степенью выраженности нефропатии [72].…”
Section: ïàòîãåíåòè÷åñêèå àñïåêòû âëèÿíèÿ áàðèàòðè÷åñêèõ îïåðàöèéunclassified